Phosphodiesterase 4 (PDE4) Inhibitors in the Treatment of COPD: Promising Drug Candidates and Future Directions - Parikh, Naisargee; K. Chakraborti, Asit (Current Medicinal Chemistry, 2016)
The PDE4 enzyme has been proven to be a versatile drug target for therapeutics to treat diverse disease conditions such as asthma, COPD, diabetes, Huntington’s disease, and various other inflammatory disorders. The treatment of COPD is the most studied utility for PDE4 inhibitors due to their ability to inhibit inflammatory cell responses. Roflumilast is the only approved drug belonging to this class to treat COPD and has shown significant results in the treatment of asthmatic patients. This perspective highlights the pharmacological details of roflumilast and cilomilast. Moreover, efforts have been made to justify the superiority of roflumilast over cilomilast by detailed comparison of their pharmacological, pharmacokinetic, pharmacodynamic properties and structural features. Several other molecules, with promising PDE4 inhibitory activity have also been highlighted. Commonly associated side effects with this class of compounds, their management, and future direction towards the development of PDE4 inhibitors with improved therapeutic index are the focus of this perspective. More emphasis has been given towards the future development strategies to limit the side effects such as emesis and to achieve better benefit to risk ratio.
Keywords: PDE4 inhibitors pipeline